Administration of Government Primary Schools in Dhaka District during the Pandemic: Strategies, Challenges, and Scopes of Improvement (Jagannath University Journal of Arts, 2026)
The study explores how school administrators adjusted to the sudden disruptions in education, oversaw remote learning initiatives, and extended support to teachers and students during this difficult time. The qualitative data collection and analysis involved 19 respondents as primary informants. Utilizing a basic interpretive qualitative research design and purposive sampling with semi-structured interviews, the research emphasizes the qualitative nature of the findings. The researcher has chosen purposive sampling in accordance with the non-probability sampling process. Semi-structured interview tools were used in data collection. Teachers began delivering instruction from their homes using apps like IMO, WhatsApp, and Zoom, but student involvement was low owing to a lack of resources, financial constraints, technological illiteracy, migration, and motivation. Despite the challenges, teachers and students agreed that contemporary digital literacy instruction, focused on regular communication and individualized feedback from teachers, can enable a school to function even in the midst of the COVID-19 pandemic.Jagannath University Journal of Arts, v-15, i-2, 2025:p108-118